Implementasi Aplikasi Presensi Mobile Dengan Pengenalan Wajah Dan Lokasi - Ilhami, Mohamad; Assegaff, Setiawan (Jurnal Manajemen Sistem Informasi, 2022)
The attendance application is an application to record employee attendance in the organization. Usually attendance uses a special tool that can record fingerprints that are placed in the office. The equipment is placed in the office and connected to the internal network in the office. This is felt to be less flexible because it creates queues at attendance times. For an organization with many locations and buildings scattered and far apart, this requires a lot of equipment which must be installed in each office location. The application works by taking photos of employees along with the coordinates of the employee's location. The employee's photo is matched with the employee's photo reference. If the photos match, then the photo is accepted as evidence of being present. The coordinates of the employee's location are matched with the campus area expressed in polygons. If the employee coordinates are in the campus area and attendance is allowed on the campus, the employee's presence is accepted. By using mobile application, the employee’s photo is valid and employees can make attendance using a cellphone regardless of the office internet connection.